The status and strategies of game teaching on Chinese course in primary schools - Li, Mu Chen; Mustakim, Siti Salina; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
In the 21st century, driven by the in-depth development of new curriculum reform, educators have gradually applied various games into classroom teaching in primary schools. However, the application of game teaching faces multiple challenges in the Chinese classroom. This study concerns the issues of implementation of game teaching and explores different strategies to motivate students' participation. Based on the review of literature, the researcher propose suggestions to improve teachers' capacity of gamification teaching, and helps to build an engaging learning environment for primary students.